Anxiety in Pregnancy: A Literature Review - Fahma, Hilmia (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background. Pregnant women commonly faced anxiety. Not only affect their maternal health, but also contribute significantly foetus development. Identifying the contributing factors will drive to specific interventions given to the patients. Methods. We search from Pubmed and Google Scholar database using relevant keywords, such as